Variability analysis of impedance matching network - CHUNG, B (ELSEVIER SCI LTD, 2006)
This paper investigates the L network impedance matching analytically. The equation describing the effect of load impedance variation on the impedance matching performance is derived. The deviation from perfect match is proportional to the variation in load reflection coefficient. However, if the load impedance is too large or too small, resulting in a large reflection coefficient, the solution to the impedance matching problem will have poorer quality in term of variability. The variability factor increases rapidly when the load reflection coefficient is larger than 0.7. A small variation in the load impedance will cause a large deviation from perfect match. (c) 2006 Elsevier Ltd. All rights reserved.